Diseño de un modelo para el sistema de distribución bajo el enfoque de logística inversa en las organizaciones productoras de envases tereftalato de polietileno PET en Bogotá, Colombia (2014)
Usually when we talk about distribution you think about of the transport process of finished products to merchants or consumers. However, the field of Reverse Logistics ineludes a complete distribution. It means manage flows and transfers of materials or products from the supplier to the consumer and plan and implement the collection of waste generated in any link in the supply chain. Therefore, this proposal presents the design of a descriptive model that ineludes some of the considerations that the organizations may to consider to manage the collection of packaging waste produced in PET or HDPE, with a view to a later insertion such a transformation process or recovery.